Cash demand in times of crises - Gerhard Rösl; Franz Seitz (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2021)
In this paper, we focus on the role of different types of crises (technological crises, financial market crises, natural disasters) and their effects on the demand for cash in an international context. It becomes evident that over the past 30 years cash demand always increased in times of crises, independent of the nature of the crisis itself.However, the type of crises determines whether small or large banknote denominations are affected more. In case of payment uncertainties, we find a crisis-related increased demand for small denominations, probably reflecting an increased demand for transaction balances. In times of uncertainties regarding the financial and/or general economic development (also possibly driven by natural disasters), large banknote denominations were comparatively more in demand indicating that the crises-related need for non-transaction balances was the dominant driver.
Keywords: E41; E51; E58; 330; Cash; banknotes; crises; Covid